NATURAL HISTORY AND TREATMENT OF DEEP-SEATED BRAIN ARTERIOVENOUS MALFORMATIONS: NATURAL HISTORY AND TREATMENT OF DEEP-SEATED BRAIN ARTERIOVENOUS MALFORMATIONS - Muhammad Rosyidi, Rohadi; Firdiansari, Alifia; Priyanto, Bambang; Januarman; Hadi, Surahman (Lombok Health And Science Journal, 2024)
Background: Brain arteriovenous malformations (AVM) might be asymptomatic. The unruptured AVM was commonly found in patient with symptoms like persistent headaches and seizure. The ruptured AVM was 35.5% annually and usually involved deep and large structures. Spetzler-Martin grading system was commonly used to evaluate the outcome and treatment options of AVM. Aim: this case report will provide information about Spetzler-Martin grade III AVM in a 26-year-old male patient with a history of throbbing headaches and a history of VP shunt procedure. Case: A 26-year-old man with the main complaint of a headache that felt like it was throbbing and continuous. Nausea and vomiting were present. History of similar complaints in 2015. History of VP shunt in 2015 due to hydrocephalus. In the head CT scan we found an iso-hyperdense lesion of ill-defined density involving the left thalamus, left basal ganglia. After adding contrast, a serpiginous tubular lesion was seen forming a nidus size Â±AP 2.77 x LL 1.96 x CC 3.72 cm with draining veins in the vein of Galen, a hyperdense lesion appears filling the left lateral ventricle and third ventricle, a VP shunt is installed through the right frontal region with the distal end in the left lateral ventricle. Discussion: Our patient was diagnosed with Spetzler-Martin grade III which has to be treated multimodally such as pre-surgical endovascular embolization followed by microsurgery or radiosurgery. Endovascular embolization may reduce the risk of bleeding in the following surgery Conclusion: Bleeding is commonly found in AVM, consisting of half of the total cases. The risk of bleeding increase in deep and large structure of AVM in the brain, usually found in Spetzler-Martin grade III. Keyword: AVM, Spetzler-Martin Grading System, Deep